A RETROSPECTIVE PHARMACOVIGILANCE ANALYSIS AT TERTIARY CARE HOSPITAL: AN OBSERVATIONAL STUDY - GIRI, KIRAN; PALANDURKAR, KAMLESH; GIRI, REENA; AGRAWAL, UDITKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Pharmacovigilance Program of India is a robust program extending from government hospitals to non-government hospital for implementation of policy of safe and rational use of drugs and early signal generation for adverse effects of drugs. Department of Pharmacology, Institute of Medical Sciences, Banaras Hindu University is part of this program since 2004. Retrospective analysis of adverse drug reaction (ADR) reported to the adverse drug monitoring center at tertiary Care Hospital. Methods: The study site was Sir Sundar Lal Hospital, Institute of Medical Sciences Banaras Hindu University, Varanasi. The study was performed after the approval of the Institutional Ethics Committee, letter number: Dean/2020/EC/2153. It was a retrospective observational study. Data collected through VigiFlow software in standard IPC Pharmacovigilance Program of India prescribed suspected ADR form, from March 2020 to June 2021 were analyzed. Causality assessment was done using a World Health Organization Uppsala Monitoring Center scale. Results: In the present study, the percentage of male patients affected is 58% and 42% female patient got suffered from adverse drug effects. About 64% of adverse effect are in possible category followed by probable, that is, 36%. The majority of adverse effects are due to antimicrobials, that is, Cephalosporins and Antitubercular group of drugs. About 20.1% adverse events show gastrointestinal symptoms. In the present study, we also observed that 5.17% adverse effects are due to hydroxychloroquine account for gastritis, headache, lethargy, and vomiting which were prescribed as prophylactic drug for COVID-19. Conclusion: Medicine information OPD in every medical college is the need of the hour to increase awareness regarding adverse events. It is important to spread importance of reporting adverse events by spontaneous reporting under Pharmacovigilance Program of India to detect rare and unusual side effects.